Bacteremia in systemic lupus erythematosus: Risk factors, clinical and microbiological characteristics, and outcomes in the largest single-center retrospective cohort in Japan. (December 2021) - Kogami, Masahiro; Abe, Yoshiyuki; Shimada, Yosuke; Hori, Satoshi; Tada, Kurisu; Yamaji, Ken; Tamura, Naoto
Background: In patients with systemic lupus erythematosus (SLE), infections, especially bacteremia, can occur throughout the course of the disease and are often fatal. We evaluated the characteristics of patients with bacteremia and SLE. Methods: In this retrospective single-center observational study, we analyzed bacteremia in 65 patients with SLE. We compared the group that survived to the group that died. To compare demographic and clinical characteristics between groups, the Mann–Whitney U test was used for non-normally distributed variables. Categorical variables were compared using Fisher's exact test. Results: The median observation period was 39 (interquartile range: 6–74) months. The median age was 54 (43–64) years. Patients consisted of six males and 59 females. In 49 cases, the patient survived. In 16 cases, the patient died. The dead group was older, with lower Glasgow Coma Scale scores, higher sequential organ failure assessment (SOFA) scores, and lower fibrinogen levels. Conclusion: When physicians encounter patients with suspected bacteremia, they should pay attention to the consciousness assessment and SOFA score, and be aware of infections caused by common microorganisms and opportunistic infections.